Penerapan Permainan “Mana Aku” Untuk Meningkatkan Kemampuan Kognitif Memahami Konsep Lambang Bilangan - Asmaul Husnah (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Abstract: The purpose of this study was to determine the increase in children's cognitive abilities in understanding the concept of number symbols through the game "Where am I". Data obtained from interviews, observations and documentation. The research subjects were children of group B of Kindergarten Aisyiyah 7 Malang. Based on the results of observations, the data obtained in the pre-action class completeness reached 50%, the first cycle became 78% and the second cycle became 95%. Based on these data, the researcher concluded that the game "Where I am" can improve children's cognitive abilities in understanding the concept of number symbols.